2004
DOI: 10.1002/lapl.200310060
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical treatment of the resonant hyper-Raman effect in a CdS crystal

Abstract: A theoretical analysis for the resonant hyper-Raman scattering (RHRS) of light in a CdS crystal is presented. The different scattering mechanisms are considered and the cross section of the RHRS by LO phonons are calculated as a function of incident frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Theoretical analysis for the first-order HRS observed was performed by us [21]. It has been shown that the mea- sured frequency dependence of the intensity of the HRS by 1LO phonons agrees with the resonance profile calculated for the hyper-Raman process caused by the twophoton transition to a s-exciton state [21].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Theoretical analysis for the first-order HRS observed was performed by us [21]. It has been shown that the mea- sured frequency dependence of the intensity of the HRS by 1LO phonons agrees with the resonance profile calculated for the hyper-Raman process caused by the twophoton transition to a s-exciton state [21].…”
Section: Discussionmentioning
confidence: 72%
“…In calculations we used the crystal parameters given in [21]. Also we took into account that this mechanism of the 2LO-scattering is weakly dependent on q LS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the forbidden Fröhlich interaction of the LO-phonons with the s-excitons of the B and C series can contribute to the HRS process too. Similar calculations of the frequency dependency of the cross section were earlier performed us, taking into account the resonant scattering process only20 . In this work the non-resonant contribution, ignored.…”
mentioning
confidence: 83%
“…In this work the non-resonant contribution, ignored. By using the crystal parameters given in Ref 20,. we carried out calculation of S HR under two-photon excitation below and in the range of the excitonic resonances.…”
mentioning
confidence: 99%
“…In particular, an increase in the HRS intensity was observed in a CdS crystal when the doubled frequency of the exciting radiation approached the exciton resonance region [10]. Later, this phenomenon was explained by the scattering mechanism caused by two-photon transitions into excitons of the s-type [11]. In recent years, the HRS spectroscopy was applied to study complex molecules [12,13], quantum dots [14], and nanoparticulates [15].…”
Section: Introductionmentioning
confidence: 99%